Efectos del cloruro de mercurio (HgCl2) sobre la sobrevivencia y crecimiento de renacuajos de Dendrosophus bogerti (2010)
ABSTRACT: Frog larvae (Dendrosophus bogerti) were exposed to ve lethal (0.25, 0.3, 0.36, 0.43, and 0.51 mg/l) and four sublethal concentrations (0.02, 0.04, 0.08, and 0.10 mg/l) of mercury chloride (HgCl2), in order to determine the LC50 and effects on growth and development rates. The LC50 at 96 h of HgCl2 was 0.41 mg/l. There was evidence for an effect of Hg on growth (weight and length) at 10 and 20 days of exposure to 0.04, 0.08, and 0.1 mg/l HgCl2 with a P < 0.001. In contrast, weight and length of tadpoles exposed to 0.02 mg/l HgCl2 showed no signi cant differences with the negative control (P = 0.77 and P = 0.1, respectively). The highest growth inhibition was observed at 30 days (P < 0.001). The time to reach Gosner stage 36 was significantly different in all specimens treated with Hg compared to controls (H = 35.4, P < 0.001). The delay in development may be related to an enzymatic alteration and in nature may have a negative impact on the survival of tadpoles due to rapid drying of temporary ponds and increased vulnerability to predators. The species D. bogerti is sensitive to mercury exposure in aquatic environments, with adverse effects on growth and development rate.